1993
DOI: 10.1104/pp.101.2.641
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Abscisic Acid in Ethylene-Induced Cotyledon Abscission in Cotton Seedlings

Abstract: Cotton (Cossypium hirsutum L. cv LG102) seedlings raised from seeds exposed to 100 WM norflurazon (NFZ) during imbibition contained reduced levels of free abscisic acid (ABA) and were visibly achlorophyllous. Exposure of untreated cotton seedlings to ethylene concentrations >1 pL/L for 24 h resulted in cotyledon abscission. In contrast, exposure of NFZ-treated seedlings to concentrations of ethylene 550 wL/L elicited no cotyledon abscission. Application of ABA, an ABA analog, or jasmonic acid to NFZtreated see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…However, the inhibition required high levels of NBD (2000 ,al L -' ) and a threshold concentration of ABA (0 .25 mM) that were only sufficient to achieve 30% abscission in the treated explants . Yet, the same concentration of NBD completely inhibited any abscission in explants treated (Table 4) as reported by Suttle and Hultstrand [24] for cotton cotyledonary node explants . The increased sensitivity to hormoneinduced abscission including ABA and ethylene has been associated with declining auxin concentrations at the abscission zone [10,11,15,16] .…”
Section: Discussionsupporting
confidence: 56%
“…However, the inhibition required high levels of NBD (2000 ,al L -' ) and a threshold concentration of ABA (0 .25 mM) that were only sufficient to achieve 30% abscission in the treated explants . Yet, the same concentration of NBD completely inhibited any abscission in explants treated (Table 4) as reported by Suttle and Hultstrand [24] for cotton cotyledonary node explants . The increased sensitivity to hormoneinduced abscission including ABA and ethylene has been associated with declining auxin concentrations at the abscission zone [10,11,15,16] .…”
Section: Discussionsupporting
confidence: 56%
“…In other plant species, a relationship among ABA, ethylene and leaf abscission has been reported (Goren et al 1993;Suttle and Hultstrand 1993;Gómez-Cadenas et al 1996). In citrus plants subjected to severe water stress, high levels of ABA were required to initiate ACC accumulation in roots and to induce its oxidation to ethylene in shoots after re-watering (Gómez-Cadenas et al 1996).…”
Section: Discussionmentioning
confidence: 96%
“…Previous results from this laboratory have demonstrated that the sustained synthesis and action of ABA are essential for the establishment and maintenance of microtuber endodormancy (Suttle and Hultstrand, 1994). Both ABA and ethylene interact in the regulation of other physiological processes, including the expression of certain wound-induced genes and the regulation of leaf abscission (Hildmann et al, 1992;Suttle and Hultstrand, 1993;O'Donnell et al, 1996). The nature and extent of the interaction of ABA and ethylene in tuber endodormancy regulation is unknown.…”
Section: Discussionmentioning
confidence: 99%